Elemental Nanoanalysis of Interfacial Alumina–Aryl Fluoride Interactions in Fullerene‐Free Organic Tandem Solar Cells. Issue 20 (16th August 2019) - Hoefler, Sebastian F.; Haberfehlner, Georg; Rath, Thomas; Canteri, Roberto; Barozzi, Mario; Hofer, Ferdinand; Trimmel, Gregor
Abstract: The choice of the optimum combination of materials for the absorber layers, electrodes, as well as interfacial layers is highly important to enhance further advances in the field of organic photovoltaics. Usually, these materials are assumed to be stable under the applied processing steps for the fabrication of the solar cells. Herein, organic tandem solar cells are examined with fluorine‐containing absorber layers consisting of the fluorinated polymer donor PTB7‐Th and the indacenodithiophene‐type small molecule acceptor O‐IDTBR and MoO3 /Al/PFN‐Br as recombination layer. Although both subcells comprise the same low bandgap absorber materials, the tandem solar cells reveal high open‐circuit voltage values approaching 2 V. However, using a combination of scanning transmission electron microscopy nanoanalysis techniques and secondary ion mass spectrometry with depth profiling, an unexpected phenomenon is disclosed. It is found that significant amounts of fluorine are accumulated in the recombination layer region which originates very likely from alumina–aryl fluoride interactions responsible for a partial defluorination of the conjugated polymer in the absorber layer. Abstract : Interfacial phenomena play a critical role in organic electronic devices. Scanning transmission electron microscopy nanoanalysis and secondary ion mass spectrometry measurements on high‐voltage organic tandem solar cells comprising a fluorinated absorber material and an aluminum‐containing recombination layer reveal the accumulation of fluorine in the recombination layer.